2019
DOI: 10.1128/aem.01614-19
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Metabolic Responses of Freshwater and Brackish-Water Strains of Microcystis aeruginosa Acclimated to a Salinity Gradient: Insight into Salt Tolerance

Abstract: Proliferation of microcystin (MC)-producing Microcystis aeruginosa in brackish waters has been described in several locations and represents a new concern for public and environmental health. While the impact of a sudden salinity increase on M. aeruginosa physiology has been studied, less is known about the mechanisms involved in salt tolerance after acclimation. This study aims to compare the physiological responses of two strains of M. aeruginosa (PCC 7820 and PCC 7806), which were isolated from contrasted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 74 publications
6
34
1
Order By: Relevance
“…The strain PCC 7806 exhibited a higher salt tolerance (up to 8.4) with no negative growth rate at higher salinity conditions. Hence, as previously observed, these two strains exhibited distinct salt tolerances, with the freshwater PCC 7820 strain less tolerant compared to the brackish PCC 7806 one [30].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The strain PCC 7806 exhibited a higher salt tolerance (up to 8.4) with no negative growth rate at higher salinity conditions. Hence, as previously observed, these two strains exhibited distinct salt tolerances, with the freshwater PCC 7820 strain less tolerant compared to the brackish PCC 7806 one [30].…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, sucrose is not only accumulated in M. aeruginosa as a response to salt shock. Indeed, it also constitutes a long-term response in salt-tolerant strains as a key metabolite during salt variation [18,30]. Despite the fact that trehalose was identified in M. aeruginosa PCC 7820, it was not significantly accumulated in response to salt stress contrary to what we previously found with acclimated cultures [30].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Recently, Tanabe, Hodoki, Sano, Tada, and Watanabe (2018), Tanabe, Yamaguchi, Sano, and Kawachi (2019) showed that some genes involved in the synthesis of sucrose could be responsible for the salinity resistance of M. aeruginosa strains from brackish waters and that their presence could be related with horizontal gene transfer (HGT). Moreover, Des Aulnois et al (2019) also identified an accumulation of trehalose in freshwater strains grown in high salinity, concluding that the use of one or other solute to maintain osmotic equilibrium could be one of the causes of the difference in salt tolerance of M. aeruginosa strains, as well as horizontal gene transfer events. Clearly, more studies to explore the limit of resistance of different M. aeruginosa strains isolated from water bodies with diverse salinity levels are still necessary.…”
Section: Discussionmentioning
confidence: 99%